Synthesis, Magneto-Spectral and Thermal Studies of Cobalt(II) Complexes of 4-[N-(Benzalidene)amino]antipyrine thiosemicarbazone and 4-[N-(2´ -Hydroxybenzalidene)amino] antipyrine thiosemicarbazone - Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
Reactions of CoX2 (X = Cl, NO3, NCS, CH3COO or CIO4) with 4-[N-(benzalidene)amino] antipyrine thiosemicarbazone (BAAPTS) or 4-[N -(2' -hydroxybenzalidene )amino ]antipyrine thiosemicarbazone (HBAAPTS) yielded complexes of the type CoX2·(L)·H2O or Co(CIO4)2·2L (L = BAAPTS or HBAAPTS). The infrared spectra of these complexes indicate that the thiosemicarbazones behave as neutral tridentate (N,N,S) ligands. All the complexes are six-coordinated according to the data of magnetic and electronic spectral measurements.